Generational time: contempory trends and trensformations (Journal of Philosophy Culture and Political Science, 2025)
The article explores the significance of the social role and cultural situation of generational cohorts. With the emergence of each new generational cohort, the cultural situation changes, and there is a change of sociocultural forms and practices (habitus). The problem is not the conflict of generations, but the conflict of the idea of coexistence of three generational groups in one social and political space. Generational discourse is the realization of the form and embodiment in everyday and social practice of the original ontological and anthropological ideas, primarily the ideas of man. In modern post-industrial societies, the lines of socio-mental generational confrontation are possibly a misunderstanding of the genesis and essence of technological change. In traditional societies, this process as an instrument of development is characterized only by the manifestation of reaction with carnival consciousness, the impotence of creativity. The existential search for freedom is unfolded by indifference to the essence of human manifestation, and in this sense, on a sharp gap in generational continuity: strengthening of religious conservatism, moral degradation of personality, and adaptation to corruption risks. The article analyzes the valueKeywords: generational time, socio-political development of society, being, generational groups